THE EFFECT OF PROBLEM BASED LEARNING (PBL) STRATEGY ASSISTED WITH LINKTREE ON COMPUTER SYSTEM LEARNING RESULTS IN STUDENTS OF MTsN 3 LANGKAT - Nasution, Haris (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
This research aims to determine whether the learning outcomes of computer systems for students taught with the Problem-based Learning (PBL) learning strategy assisted by Linktree are better than the learning outcomes of students taught with the Expository learning strategy in class IX MTsN 3 Langkat. The research was a quasi-experiment, involving two classes that were given different treatments. The research design used in this research is Pre-test Post-test control group design, namely by looking at the differences in influence on post-test learning outcomes between the experimental and control groups. Statistically, using the t-test, it was concluded that the learning outcomes of students who were taught using the Linktree-assisted Problem Based Learning (PBL) Learning Strategy were better than the learning outcomes of students who were taught using the expository strategy in informatics subjects at MTsN 3 Langkat in systems material. computer, this is proven from the results of hypothesis testing where tcountttable, namely 13.771.666.